Revision of the Late Permian Non-Marine Bivalve Genus Verneuilunio Starobogatov, 1987 - M.N. Urazaeva; V.V. Silantiev; R.R. Usmanova (Учёные записки Казанского университета: Серия Естественные науки)
The genus Verneuilunio (type species Naiadites verneuili) has been singled out from the genus Palaeanodonta Amalitzky based on differences in the structure of hinge margin established using the literature data. Both genera have been included in the family Palaeanodontidae, which used to be considered by the discoverer of this genus as a subjective synonym for the family Palaeomutelidae. The revision of W. Amalitskii’s collection has demonstrated that the original diagnosis of the genus con-tains a number of inaccuracies. This creates difficulties for identification of the genus Verneuilunio and complicates its placement within higher taxa. The paper presents a revised diagnosis of the genus Verneuilunio. The detailed description of its type species is provided. The genus Verneuilunio has been assigned to the family Naiaditidae based on the duplivincular and slightly amphidetic ligament. According to this feature, the genus under study is significantly different from other unio-like Late Permian non-marine bivalve genera (Palaeomutela, Palaeanodonta, Oligodontella, and Opokiella), often occurring in the same strata. The genus Verneuilunio mostly resembles some Late Carboniferous “atypical” unio-like species of the genus Anthraconaia Trueman et Weir. Statistical processing of the biometric parameters of Verneuilunio verneuili and the species A. pruvosti, mostly resembling it, has revealed statistically significant differences in elongation of the posterior end of the shell. To date, the geographic range of the genus Verneuilunio is restricted to the central part of the East European Platform, whereas its stratigraphic range is in the lower sublayer of the Severodvinsk layer.